1995
DOI: 10.1007/bf02276632
|View full text |Cite
|
Sign up to set email alerts
|

Eine kritische Bewertung der funktionellen Behandlung von Kollumfrakturen bei Kindern

Abstract: In this retrospective follow-up study after 6 months of treatment with functional appliance therapy of 12 children who had suffered condylar fractures, spiral CT was employed for the radiological examination with 2D and 3D reconstructions. Although all patients exhibited restoration of normal function, only 4 showed favorable remodeling. The other patients had developed 5 hypoplastic, 5 moderate and 5 severe deformed condyles. Seven condylar fragments were resorbed; 2 were uprighted; 4 had developed bony spurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
1
7
0
6
Order By: Relevance
“…Various authors have investigated the interdependence between fracture type and healing outcome [5,6,7,11]. There is general consensus that good results can be achieved subject to only minor dislocation and prolonged functional follow-up treatment [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various authors have investigated the interdependence between fracture type and healing outcome [5,6,7,11]. There is general consensus that good results can be achieved subject to only minor dislocation and prolonged functional follow-up treatment [1].…”
Section: Discussionmentioning
confidence: 99%
“…Kahl-Nieke et al [6,7] reported in a follow-up study very good functional results only 6 months after minor dislocation or high fractures. However, complete restoration of the structures was observed in only one fifth of the collective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Durch spiralcomputertomographische Analyse der Kiefergelenkmorphologie sollte der in der einschl~.gigen Literatur beschriebene Zusammenhang zwischen Alter sowie Frakturtyp und kondy-I~.rer Remodellierung quantifiziert werden. Whereas Hirschfelder [6] found new bone formation and reshaping of condyles in 61% of her follow-up patients with previous condylar fractures, quantitative analysis of spiral CT reconstructions showed deformed condyles in 67% of the Cologne follow-up patients [9,11,13]. Die Kondylusgr68e und die Kolluml~,nge der ipsi-und kontralateralen Kiefergelenke wurden auf den axialen und parasagittalen Rekonstruktionen gemessen und geschlechts-, alters-und frakturtypspezifisch verglichen.…”
unclassified